Analysis of integrability of the generalyzed Kadomtsev-Petviashvili type model - Pritula, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
The existence of the Lax representation is established for the generalized Kadomtsev-Petviashvili (KP) model. One describes the class of completely integrable, two-dimensionalized equations of the KP type on operator manifolds.